NCOG-05. IMPACT OF ADDITIONAL RITUXIMAB TO STANDARD THERAPY ON COGNITIVE PERFORMANCES IN PRIMARY CENTRAL NERVOUS SYSTEM LYMPHOMA PATIENTS. (11th November 2019) - van der Meulen, Matthijs; Dirven, Linda; Habets, Esther; Bakunina, Katerina; Taphoorn, Martin; van den Bent, Martin; Issa, Samar; Doorduijn, Jeanette K; Bromberg, Jacoline E C
Abstract: BACKGROUND: The goal of treatment of primary central nervous system lymphoma patients is to improve survival, without compromising neurocognitive functioning. The aim of this study was to analyze the effect of Rituximab and low-dose whole brain radiotherapy (WBRT) on cognition. METHODS: 199 patients from a phase III trial (HOVON 105/ ALLG NHL 24), randomized to standard chemotherapy (and 30Gy WBRT for patients < 61 years-old only) with or without Rituximab, were asked to participate in a short neuropsychological evaluation (NPE) before and during treatment, and up to 2 years of follow-up or until progression. A difference in z-score, corrected for sex, age and education, of ≥ 1 point was considered as clinically relevant. The primary outcome was a difference over time between the arms in multiple cognitive domains, assessed by linear mixed models (LMM). Changes in cognitive performances between baseline and 24 months after treatment were assessed for both arms in cross-sectional analyses. Effect of WBRT was analyzed in irradiated patients only. RESULTS: 105/199 patients completed at least one NPE; baseline characteristics were similar to the total trial population. Compliance was >60% at all evaluation points. No clinically relevant differences over time between the arms were seen in all domains in LMM analysis. Comparing changes from baseline to 24 months of follow-up, mean cognitive scores remained stable in both arms for attention, executive functioning (TMT B), and information processing speed. A clinically relevant improvement was seen in both arms for executive functioning (TMT A), memory and motor speed. In the irradiated patients (n=33) all scores remained stable after WBRT, up to 24 months of follow-up in all domains. CONCLUSION: Cognitive performance remained stable or improved after treatment. Addition of Rituximab to standard treatment did not impact cognitive performance over time. After low-dose WBRT, cognition remained stable up to 2 years.